Digitization and the evolution of money as a social technology of account - Michael Peneder (Austrian Institute of Economic Research (WIFO), 2021)
From Aristotle to Ricardo and Menger, economists have emphasised the function of money as a medium of exchange together with the intrinsic qualities that increase its saleability and credibility as a most liquid store of value. But the social institution of money co-evolves with technology. It is significant that the advent of digital cryptocurrencies was initiated by computer scientists and has taken economists completely by surprise. As a consequence, it also forces our profession to rethink the basic phenomenology of money. In accordance with the views of Wieser and Schumpeter, digitization brings to the fore its immaterial function as a standard of value and social technology of account, which increasingly absorbs that of a medium of exchange. The potential impact on economic policy is huge. The variety of different crypto coins has proven the technical feasibility of competing private currencies as proposed by Hayek. In the long term, however, there is reason to doubt the persistence of intense competition. One must fear that major digital platforms will extend their current dominance in multisided virtual market places to include digital payments and money. Central banks are increasingly anxious to preserve public sovereignty over the common unit of account and consider issuing their own digital fiat money. After the current era of intense creative experimentation, the potentially new spontaneous order of private crypto-currencies is likely to be supplanted by central bank digital currencies (CBDCs), the design of which will depend on deliberate public choices and policies.
Keywords: B26; B53; G28; O11; O16; 330; Digitization; evolution of money; currency competition; general ledger; crypto coins; central bank digital currency (CBDC); Austrian economics